Existence of solutions for 2nth-order nonlinear p-Laplacian differential equations. (April 2017) - Saavedra, Lorena; Tersian, Stepan
Abstract: The aim of this paper is to study the existence and multiplicity of weak and classic solutions for a 2 n th -order differential equation involving the p -Laplacian coupled with periodic boundary conditions. The results are proved by using the minimization argument and an extended Clark's theorem. Some particular cases are shown.